Enhanced-view totally extraperitoneal repair in a patient with incisional hernia after robot-assisted laparoscopic radical prostatectomy: a case report - Shusaku Honma; Keisuke Tanino; Takashi Kumode; Ryosuke Mizuno; Yugo Matsui; Siyuan Yao; Teppei Murakami; Takatsugu Kan; Sanae Nakajima; Takehisa Harada (Surgical Case Reports)
Abstract Background Although laparoscopic incisional hernia repair, especially laparoscopic intraperitoneal onlay mesh, is a widely used technique, it can cause serious complications, including mesh erosion, adhesive bowel obstruction, and chronic pain. The enhanced-view totally extraperitoneal (eTEP) technique has been reported to prevent such complications by placing the mesh in the retrorectus space. Here, we report the case of a patient with post-robot-assisted laparoscopic radical prostatectomy (RARP) incisional hernia repaired using the eTEP technique. Case presentation A 67-year-old man, who underwent RARP for prostate cancer 4 years ago developed an incisional hernia. Abdominal computed tomography showed the presence of an epigastric incisional hernia measuring 4 cm long and 3.7 cm wide. We performed an eTEP repair. We closed the hernia defect using a 0 barbed suture and placed a self-gripping mesh measuring 20 cm long and 15 cm wide in the developed retrorectus space with no fixation. There were no postoperative complications, and the patient was discharged on postoperative day 2. Conclusions eTEP repair is considered an extremely effective surgical treatment option for incisional hernias because of its few resulting postoperative mesh-and-tacker-related complications.